IMPLEMENTASI SMART PARKING BERBASIS WIRELESS SENSOR NETWORK DENGAN INTEGRASI LORA DAN LIDAR - Kazhim, Musa Al; Busran, Busran; Putra, Eko Kurniawanto; Warman, Indra; Syahrani, Anna (STKIP Pesisir Selatan, 2025)
In response to this critical issue, this study aims to implement and evaluate a prototype of a smart parking system based on a Wireless Sensor Network (WSN), integrating Long Range (LoRa) communication and Light Detection and Ranging (LIDAR) technology. A quantitative experimental approach was employed in developing the system, where the prototype was designed using the TF Luna LIDAR sensor for precise vehicle detection, the LoRa RA-02 module as a long-range wireless communication medium between nodes, an Arduino Nano or ESP32 microcontroller as the data processing unit, and infrared (IR) sensors to detect gate barrier conditions. Comprehensive testing was conducted in a simulated parking area to measure vehicle detection accuracy, sensor response time, and wireless communication efficiency. The results demonstrate highly promising performance: the LoRa RA-02 module successfully transmitted data stably up to approximately 200 meters in a basement environment, proving its superiority in coverage and power efficiency compared to conventional wireless technologies. The TF Luna LIDAR sensor achieved high detection accuracy with an average measurement error of only about 1–2 cm, making it more reliable than ultrasonic sensors, although precise placement was required due to its 1.5-meter range limitation.